Modelling of Processing Steps of New Generation ODS Alloys - Svoboda, J.; Horník, V.; Riedel, H. (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2020)
The paper describes the processing of an oxide-dispersion strengthened (ODS) alloy with the chemical composition Fe-10Al-4Y 2 O 3 . A creep-resistant microstructure with coarse grains and a high volume fraction of finely dispersed oxides is obtained by a processing chain consisting of mechanical alloying of the powder, consolidation by hot rolling and subsequent annealing at 1200 °C. To understand the processes underlying the microstructural evolution during hot rolling and annealing, a model for strain hardening, recovery, recrystallization and grain growth is adapted. The quantitative model is able to describe the observed microstructural features and allows identifying processing windows in which the desired microstructure can be achieved.